2021
DOI: 10.1177/0954406220980502
|View full text |Cite
|
Sign up to set email alerts
|

Effects of segmented layer suction and micro-vortex generator on a high-load compressor cascade performance

Abstract: The axial location of full-span boundary layer suction is studied to explore the influences of suction slot on the cascade performance. At the design condition, the slot with 50% axial location shows a superior capability to reduce the total pressure loss. At the near stall condition, the more upstream of the suction slot is moved, the more total pressure loss is reduced, and the suction slot with a location of 0.7 axial chord length cannot effectively reduces the total pressure loss in all conditions. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The two-equation shear stress transport (SST) k-ω eddy viscosity model was selected to model the effect of turbulent flow. Previous studies of Langtry et al, 31 Kan et al 32 and Ma et al 33 indicated that this turbulence model predicted the corner separation flows in compressor cascades with acceptable accuracy. The γ-θ transition model was introduced to simulate the SS laminar transition phenomenon observed in the previous experiments.…”
Section: Numerical Setupmentioning
confidence: 77%
“…The two-equation shear stress transport (SST) k-ω eddy viscosity model was selected to model the effect of turbulent flow. Previous studies of Langtry et al, 31 Kan et al 32 and Ma et al 33 indicated that this turbulence model predicted the corner separation flows in compressor cascades with acceptable accuracy. The γ-θ transition model was introduced to simulate the SS laminar transition phenomenon observed in the previous experiments.…”
Section: Numerical Setupmentioning
confidence: 77%
“…Studies have revealed that this design can reduce the total pressure loss in a cascade by 11.2% and increase the static pressure by 9.84%. Ma et al [16] proposed a novel segmented suction slot design for blade suction sides and revealed that with increases in the incidence, the corner separation range near the suction side gradually expands along the span and chord directions. Furthermore, the separation point also continues to move forward, and before a stall occurs, this separation range always includes the corner region formed by the end-wall and the blade's trailing edge.…”
Section: Introductionmentioning
confidence: 99%
“…12. Top view of the blade with plenum and slot.Refers to the literature referenceMa et al (2021), a segmented suction slot is selected in this research.Figure13shows the distribution of the segmented suction slots. The airflow is sucked in the plenum by the five section suction slots, and the airflow out of the plenum has a 1% suction mass-flow ratio.…”
mentioning
confidence: 99%